Pengaruh Pengetahuan Keuangan Dan Gaya Hedonisme Terhadap Perilaku Keuangan Mahasiswa Akuntansi - Susilawaty, Eka Astra (Pascasarjana STIE Amkop Makassar, 2024)
Financial freedom requires every generation to be able to manage their finances well. Not only limited to adults, this also applies to today's young generation for future financial well-being. Good financial management certainly requires qualified financial knowledge. Accounting students are students who have certainly been forged with various financial knowledge. However, despite the existence of financial knowledge possessed, it does not guarantee that students will manage finances well. Moreover, currently there are two magic mantras that are being viral by the younger generation, namely YOLO and FOMO. Adopting these two mantras, students tend to have a lifestyle of hedonism. This study aims to determine the effect of financial knowledge and hedonism lifestyle on generation Z's financial management behavior. This research is a quantitative study whose population is students of the Accounting Department of the State Polytechnic of Ujung Pandang. The research sample was determined by purposive sampling technique using the Slovin formula. Data collection was obtained using a questionnaire in the form of a google form. Partial research results show that financial knowledge has a positive and significant effect on financial management behavior while hedonism lifestyle has no influence on the financial management behavior of accounting students. This indicates that the higher a person's financial knowledge, the wiser they are in managing their finances. But simultaneously, the results showed that both variables affect financial management behavior.Keywords: Financial Knowledge, Hedonism Lifestyle, Financial Management Behavior